BLOOD SMEAR SCAN IN LOW PLATELET COUNTSWHAT DO WE GAIN? – PATHOLOGIST’S PERSPECTIVE - DR.SUBHASHREE A.R., (International Journal of Pharma and Bio Sciences, 2014)
When the hematology analyzer gives a low platelet count, peripheral smear screening is often conducted by a Hemato morphologist for manual platelet estimate to counter check the analyzer’s report. Such a smear screening process is often considered as an additional burden. This prospective study was conducted to analyze whether it is worthwhile to attach emphasis on such platelet ‘scans’ in low platelet counts.